El problema de la territorialidad en el estudio de la conquista de Ceilán - Zoltán Biedermann (Mélanges de la Casa de Velázquez, 2018)
This article addresses all the methodological challenges related to the study of the territorial conquest of Sri Lanka, generally known in modern Spain as Ceylon. This island was the target of a policy of conquest promoted by the imperial authorities in Goa, Lisbon and Madrid between 1594 and 1638. What the imperial authorities failed to realise was that there wa no territorial logic to the political make-up of Sri Lanka. Understanding this different anthropological logic, in which political power is not necessarily expressed through the constitution of territories, is the first step towards a historiographic reconstruction of the period when the conquest took place and an understanding of it in connection with other Habsburg conquests in the New World.